Lessons in suffering: Greek tragedy's teachings on disability through Sophocles' Philoctetes. Issue 3 (2nd July 2016) - Gagnon, Jennifer M.
Abstract: Political theory often sees disability through the negative language of abnormality and inability, which perceives disability as a deficiency that deviates from the able-bodied. However, critical disability studies strives to transform the disabling language of political theory into an enabling project that sees the ability, unique perspectives, capacities, and contributions of people with disabilities. Through Sophocles' Philoctetes, this article examines the negative ways in which disability is conceptualized, socially constructed, and (dis)valued, as well as the possibilities for a positive and enabling theory of disability. The character of Philoctetes exposes the negative social construction of disability as well as the extraordinary ability of those who live with chronic impairments. The Philoctetes meditates on the status of the disabled who are unfairly isolated from human community and who are often unfairly seen in an instrumental fashion that fails to recognize their fundamental status as human beings who are capable, valuable, and essential for the success of human endeavors and community. For political theory, the Philoctetes demonstrates the ability in disability, and shines brightly on the essential contributions that people with disabilities make in our societies. Philoctetes shows that the lives of people who live daily with chronic impairments need not be seen as necessarily tragic. Instead, these modes of being speak to human diversity, ingenuity, and triumph.